Reconceptualizing the Principle of Public Hearing in E-Litigation: Ensuring Procedural Justice in the Digital Era - Dwi Tirtousada (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the normative dissonance between the spirit of the open court principle in Law No. 48 of 2009 and its technical implementation in PERMA No. 1 of 2019 regarding e-litigation. The research employs a normative legal method with a juridical-philosophical approach to evaluate the impact of judicial digitalization on the degradation of the philosophical value of openness. The results indicate that current e-litigation practices potentially reduce the meaning of 'openness' from substantive public participation to merely passive virtual accessibility. This reduction directly impacts the decline of judicial accountability and the legitimacy of decisions in the public eye due to the loss of social control functions. As a primary contribution, this study offers a model for reconceptualizing the principle of openness based on three pillars: access, transparency, and active public participation. Through mechanisms such as interactive trial live-streaming and the E-Judicial Civic Oversight (E-JCO) platform, this model ensures that digital transformation not only guarantees document access but also preserves the essence of public oversight to achieve true procedural justice in the digital era.